Changes in stilbene composition during postharvest ozone treatment of 'Moscato bianco' winegrapes. (September 2019) - Río Segade, Susana; Vincenzi, Simone; Giacosa, Simone; Rolle, Luca
Abstract: Stilbenes, including trans -resveratrol and its derivatives, are compounds naturally present in grapes and have gained a growing interest due to reported health-promoting properties. The production of resveratrol-enriched table grapes has promoted recent research on stress-induced synthesis of stilbenes. The oxidizing properties of ozone have been successfully exploited to its use as sanitizing agent and stilbene elicitor during table grapes storage. In winegrapes, this study represents the first research focused on the effect of postharvest ozone treatments on the accumulation of stilbene compounds. The study was carried out on Moscato bianco winegrapes ( Vitis vinifera L.) and several gaseous ozone treatments were investigated differing in ozone dose (30 and 60 μL/L), exposure time (24 h, 48 h, and several days until 30% of weight loss), and delay time until processing (just after and several days after treatment). The stilbene production induced by ozone exposure was assessed in fresh and partially dehydrated winegrapes up to 5, 10, 15, 20, and 30% of weight loss aiming to evaluate the single and combined effect of oxidative and osmotic stresses. The results obtained showed that short-term exposure of fresh winegrapes at 60 μL/L of ozone for 48 h was not effective in inducing resveratrol accumulation just after treatment, but it had an elicitor effect on total stilbenes (+36%) in grapes subsequently dehydrated up to 20% of weight loss with a significant overproduction of trans -resveratrol and trans -piaceatannol. In addition, long-term and continuous treatments under ozone-enriched atmosphere can be also used during dehydration to sanitize winegrapes without affecting negatively the concentration of stilbenes. Therefore, the use of gaseous ozone during storage and dehydration could be indicated to reduce the use of sulfur dioxide and, depending on ozone dose and exposure time, the synthesis of stilbene compounds could increase. Graphical abstract: Unlabelled Image Highlights: Effect of postharvest ozone treatment on stilbene synthesis was studied in winegrapes. Several treatments were investigated differing in ozone dose and exposure time. Single and combined effects of ozone and dehydration stresses were also assessed. Ozone exposure at 60 μL/L for 48 h was effective to induce stilbenes after withering. Stilbene concentration was not affected negatively during long-term ozone treatments.